Effect of three different grip angles on physiological parameters during laboratory handcycling test in able-bodied participants - Abel, T.; Burkett, B.; Thees, B.; Schneider, S.; Askew, C. A.; Strüder, H. K. (Frontiers in Physiology, 2016)
Introduction: Handcycling is a relatively new wheelchair sport that has gained increased popularity for people with lower limb disabilities. The aim of this study was to examine the effect of three different grip positions on physical parameters during handcycling in a laboratory setting.